The Effectiveness of Additional Methods of Decompression in Patients with Supratentorial Dislocation of the Brain - Yrysov, Keneshbek; Mamytov, Mitalip; Kadyrov, Ruslan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2018)
The aim of the study is to evaluate the effectiveness of additional methods of external and internal decompression in patients with supratentorial dislocation in focal lesions of the cerebral hemispheres. Materials and methods: A retrospective analysis of 219 cases of supratentorial compression of the brain in patients hospitalized in the Clinic of Neurosurgery of the National Hospital of the Kyrgyz Republic was conducted. In the main group of 143 observations, the assessment of the severity of dislocation syndrome according to our 12-point scale was performed; according to the results of this assessment, after the eradication of the focal lesions, additional methods of external and/or internal decompression were used. The drainage of the lateral ventricles and the one-sided wide infratemporal decompressive craniotomy in severe cases supplemented by the microsurgical resection of the mediobasal parts of the temporal lobe were performed. Results: The analysis of the study showed an increase in unfavorable outcomes with the growth of the severity of DS. Thus, the gross residual effects found in stage I in 17.4% of the patients, in stage II were already found in 43.0%, and in stage IV - 69.4% of the observations. The group with fatal outcomes was even more demonstrative, which showed a clear increase in the number of deaths of patients as the severity of the dislocation progressed. Among patients with DS in stage I, 19.4% died, while in stage III - 32.1 %, and in stage V (the most severe) – 2 of 3 patients died, making up 66.7% of this group. The total number of deaths in both groups was 51 cases (23.2%); at that a significantly smaller percentage of failures of the treatment (p <0.05) was found in patients of the main group making up 20.2%, compared to 29.0% of the control group. Conclusion: the findings of the clinical and instrumental examinations of patients in the postoperative period confirm the high effectiveness of methods of additional external and internal decompression, a high percentage of survival of patients in the main group and a decrease in the number of deaths in the treatment compared to the control group.